Is row orientation a determinant factor for radiation interception in row vineyards?. (3rd October 2016) - Campos, I.; Neale, C.M.U.; Calera, A.
Abstract: Background and Aims: This study analysed the effect of row direction on photosynthetically active radiation (PAR) absorption (APAR) and the fraction of PAR absorbed (fPAR) on both a daily and hourly temporal scale in vertical shoot positioned trellised vineyards. Methods and Results: The analysis included experimental data and model simulations. The data of fPAR and APAR were acquired in commercial plots with a range of canopy development and with row directions near to the north–south, northeast–southwest and east–west orientations. Simulated values of fPAR and APAR were calculated for north–south, northeast–southwest, northwest–southeast and east–west row directions and for a range of geographical latitudes, from 30 to 50°N to represent the wide range of latitudes where grapes are grown round the world. In agreement with previous research, the results confirm the strong daily variation of fPAR and APAR, and the instantaneous values of these parameters are not representative of the daily period in row vineyards. The field data and model results suggest the advantage of the north–south and northeast–southwest row orientations to maximise PAR absorption for latitudes between 30 and 50°N. And the exploratory analysis based on model simulation indicates that PAR absorption is lower for the east–west row direction in all latitudes analysed. Conclusions: The interrelations between radiation regimen and physiological aspects related to climatic limitations in canopy conductance result in a relative advantage of the north–south and northeast–southwest row directions against other orientations in arid and semi‐arid environments. Significance of the Study: The determination of the potential PAR absorption for a given vineyard training system enables a good first step towards understanding the effect of canopy management on vineyard productivity. In addition, these results are of interest for plot design and simulation of vineyard development.